Finite element design of a vibrational membrane to reduce distortion in a bone‐conduction implant transducer. Issue 5 (22nd December 2021) - Shin, D. H.; Seong, K. W.; Kim, M. N.; Lee, K. Y.
Abstract: This paper describes the finite element design of a vibrational membrane with a cantilever structure to reduce distortion in bone conduction implant (BCI) transducers. To derive the optimal number of cantilevers, a model of ideally aligned components was established based on the structure of a previously proposed transducer, and mechanical vibration analysis was performed using different numbers of cantilevers (two to five). Under the same conditions, similar analyses were performed using vibrational membranes misaligned with the transducer magnet by 0.1 and 0.2 mm. Then, the standard deviations were calculated from the analysis results to numerically compare the magnitudes of vibrations between cantilevers for each cantilever shape. The larger the number of cantilevers, the smaller the standard deviation in both the alignment and misalignment cases. Moreover, from the analysis result, it was confirmed that using a vibrational membrane composed of five cantilevers can reduce distortion in BCI transducers.